EXAMINING THE RELATIONSHIP BETWEEN PRIVATE HEALTHCARE FINANCING AND POVERTY IN EDO STATE, NIGERIA - Muhammed , Musa (Economics and Statistics Research Journal (ESRJ), 2022)
Private out-of-pocket healthcare financing has been identified as having a negative impact on the income of households and contributing to poverty in Nigeria. This study focuses on Edo State and aims to analyze the effect of private healthcare financing on poverty. The study used a survey method in which a structured questionnaire was randomly administered to a cross-section of households in Edo State. Data was analyzed using descriptive and multinomial logistic regression techniques. The study found that out-of-pocket payments for healthcare were the dominant method of private healthcare financing in Edo State, leading to a negative effect on the income of households. The study recommends the introduction of an effective collective healthcare financing mechanism to reduce the financial burden associated with out-of-pocket spending. In addition, the study suggests investing in research and development of locally manufactured drugs with high local content to improve the availability and affordability of effective drugs. The importance of healthcare financing in reducing poverty is highlighted, and the impact of healthcare spending on national income growth is discussed as a theoretical framework for understanding the issue.